Transformasi Digital Dashboard Spreadsheet Pelaporan Harian dan Bulanan dalam Kemudahan Operasional - Rahimah, Rahimah; Amir, Elfi; Purwaningtyas, Dian Anggraini (TIN: Terapan Informatika Nusantara, 2025)
Digital transformation in operational data management is a strategic need for modern aviation institutions. Unit Apron Movement Control (AMC) at BLU UPBU Office Class I Aji Pangeran Tumenggung Pranoto Samarinda faced the problem of delay in data processing due to dependence on the Microsoft Excel application which shows limitations in supporting operational efficiency. This study aims to analyze the implementation of Google Spreadsheet as an alternative data processing system solution to overcome these problems and optimize information management in the AMC unit. The research method uses a comparative qualitative approach with triangulation data collection techniques, including participatory observation of the implementation of existing data processing systems, in -depth interviews with the head of the AMC unit and operational personnel, as well as documentation analysisrelevant administrative.Data was analyzed descriptively to compare the effectiveness and efficiency of the two data processing systems. The results of the study demonstrated that the implementation of Google Spreadsheet provides a significant increase in the efficiency and effectiveness of AMC unit data processing by achieving an increase in data accuracy, reduction of processing time up to 60-70%, broader accessibility, and reductionSignificant operational costs, while ensuring data security through controlled access protocols and reliable backup systems ..The advantages of the system include real-time processing capabilities, integrated collaboration facilitation between units, and error risk mitigation and delay in information processing. These findings indicate a significant potential for the use of digital collaborative platforms in increasing organizational productivity, although there are still gaps in the optimal use of information technology among practitioners who are not yet familiar with digitalization -based solutions. This study contributes to the understanding of the Best Practices of Management Information Systems Transformation in the Aviation Sector and provides practical recommendations for the implementation of digital technology in the operational optimization of work units.